Strengthening primary health care in low- and middle-income countries: furthering structural changes in the post-pandemic era - Alegre, J. C.; Sharma, Suneeta; Cleghorn, Farley; Avila, Carlos (Frontiers in Public Health, 2024)
Strengthening primary health care (PHC) is the most cost-effective public health interventionapproach in low-and middle-income countries (LMICs) to achieve sustainable universal health coverage (UHC), protect against health shocks, and promote health and wellbeing for all people. It has been 45 years since PHC was put on the global agenda followed by multiple efforts to advocate for more funding and improved performance of PHC. Yet, investment in PHC is still insufficient and overall performance of PHC systems is weak in LMICs, resulting in increased vulnerability and poor health outcomes especially among marginalized populations. As countries recover from the COVID-19 pandemic, which exposed the fragility of health system functions, including PHC platforms, it is imperative to go beyond advocacy for PHC investments and make systemic changes to strengthen PHC as the foundation of resilient and equitable health systems. We propose five gamechangers to facilitate structural changes for strengthening PHC through a focused health systems approach: [i] integration of client-centered health services at PHC level; [ii] digitization of PHC services; [iii] efficiency gains invested in essential health services; [iv] strengthening management practices for PHC at district and facility levels; and [v] community engagement for PHC. To be successful, the implementation of the gamechangers must be contextualized and focus on achieving sustainable health outcomes, and therefore use implementation approaches that link essential health services to health outcomes. Through this way countries will maximize the possibility of achieving UHC and attaining the ambitious health targets of the Sustainable Development Goals (SDGs) by 2030.